Pengaruh Edukasi Kesehatan terhadap Pengetahuan, Sikap dan Persepsi Ibu Menyusui mengenai Tempoyak sebagai Sumber Probiotik untuk Kesehatan Ibu dan Anak - Suci Rahmani Nurita; Tuhu Perwitasari; Julaecha Julaecha; Nurfitriani Nurfitriani (Jurnal Akademika Baiturrahim Jambi, 2023)
The health of the digestive system affects the human immune system by 70%. Consuming food or drinks that contain probiotics is an effort to maintain digestive tract health which can be obtained from fermented foods and drinks. Tempoyak is a kind of traditional food which is the result of spontaneous fermentation of durian (durio zibethinus) by microorganisms. Mothers are generally not familiar with the term probiotics and do not know the benefits of probiotics, this can be seen from the results of the pre-test questionnaires distributed. Based on personal interviews with 3 breastfeeding mothers at PMB Yustati Ambarita, all of them admitted that they did not dare to eat tempoyak for fear of having an effect on their milk and babies. Not all mothers know that tempoyak contains good bacteria that are beneficial for digestive tract health. This study aims to determine the effect of health education on the knowledge, attitudes and perceptions of breastfeeding mothers regarding tempoyak as a source of probiotics (LAB) for the health of mothers and children. This research method is a quasi-experimental research with a pre-post test one group design. The population of this study were all breastfeeding mothers who had babies aged 0-2 years in the working area of PMB Yustati Ambarita. The sample in this study were all breastfeeding mothers who had babies aged 0-2 years as many as 20 people. Samples were taken by purposive sampling technique. This research was conducted from October 2021 to August 2022 at PMB Yustati Ambarita. The results of the study showed that there was an average increase in the knowledge, attitudes and perceptions of the respondents between before and after being given the intervention in the form of health education. It is hoped that PMB will improve health education programs related to the importance of probiotics during the third trimester of pregnancy. It is hoped that mothers can increase their knowledge about sources of probiotics from local food, especially tempoyak